Social Support, Job Demands, and Workplace Incivility in Generation Z - Salwaa Nur Fauziyyah; Fetty Poerwita Sary (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Workplace incivility such as rudeness, exclusion, and disrespect is a growing issue, especially among Generation Z employees who are prone to stress and mental health issues. Incivility has negative consequences, including decreased productivity and increased absenteeism. This study examines the effects of job demands and social support on workplace incivility, with job stress as a mediating variable. Using a quantitative descriptive-causal research design, data were collected from 190 Generation Z employees through a structured questionnaire and analyzed using Structural Equation Modeling (SEM) with SmartPLS. The results showed that job demands had a significant positive effect on job stress, which in turn increased incivility. Conversely, social support was able to reduce job stress and incivil behavior. Job stress was shown to mediate the relationship between the independent variables (job demands and social support) and workplace incivility. These findings emphasize the importance of creating a supportive work environment and effective workload management to reduce incivil behavior and improve employee well-being, especially among younger generations.